IDENTIFIKASI MIKROPLASTIK PADA IKAN TONGKOL (Euthynnus affinis) SEBAGAI BIOINDIKATOR DI PERAIRAN TELUK KOTA KUPANG - Nitti, Fidelis; Nalle, Tamara Baba; Boymau, Benyamin; Anait, Johanes R.; Kadang, Luther; Ola, Antonius R.B.; Baunsele, Since D.; Naat, Johnson N. (Chemistry Notes, 2025)
Microplastic pollution in coastal areas has become a serious concern due to its impact on marine environments and human health. This study examined the presence of microplastics in the digestive tracts of the tongkol fish (Euthynnus affinis) collected from two locations in Kupang Bay, namely PPI Oeba and Pasar Oesapa. A total of 16 fish samples were analyzed visually using a microscope, followed by polymer identification using Fourier Transform Infrared Spectroscopy (FTIR). Results showed that fish from PPI Oeba contained 25 microplastic particles, while those from Pasar Oesapa had 20 particles. Film-type microplastics dominated, accounting for 68% in PPI Oeba and 75% in Pasar Oesapa, followed by fibers (20% and 25%, respectively), and fragments were only found in PPI Oeba (12%). Detected polymers included polyethylene (PE), polypropylene (PP), and polyvinyl chloride (PVC). This study confirms that tongkol fish can serve as effective bioindicators for monitoring microplastic pollution in the coastal waters of Kupang City.